Keanjalan penggantian antara kemahiran dalam sektor pembuatan di Malaysia - Ismail, Rahmah; Jajri, Idris (Universiti Utara Malaysia, 2004)
It is very crucial to know the elasticity of substitution among various sectors,skills and between skills and physical capital because it will help the producers in planning their manpower. The value of the elasticity of substitution between inputs is also important to policy makers because it determines the effectiveness of the policy regarding input price change. Besides this, the elasticity of substitution provides an important guideline to the education planner. This article analyses the elasticity of substitution between physical capital and labour and between various skills, namely professionals, supervisors, skilled labour, semi-skilled labour and unskilled labour in the Malaysia manufacturing sector based on the Manufacturing Survey of 1985-1996. The constant elasticity (CES) production function is used to estimate the elasticity of substitution. The results show that the elasticity of substitution for most combination inputs is greater than unity but in general they are still low. The elasticity of substitution between high rank job categories and skills is larger than the elasticity between the low rank job categories. Also more capitalintensive industries show higher elasticity of substitution between their inputs. This reflects high rank jobs like professional and technical careers are easily substituted by other skills in the production process when their price increases. Also workers in a more capital-intensive industries are more easily substituted by each other.